The effect of international oil price on LNG price in South Korea and Japan - Kwon, Hyukdong; Cho, Hong Chong (Geosystem engineering, 2018)
In this paper, we investigate the differences between LNG price of South Korea and Japan. Although S. Korean and Japanese LNG markets have similar structures, there are some differences in the price formation. From DCC-MGARCH, we confirm that Japan LNG price have less persistence of disturbance on time than S. Korean LNG price. The conditional correlation also shows linkage effects between LNG prices and impacts of S-curve and DS-curve. Moreover, ARDL estimation result shows that there is co-integration in all models and that impacts of Fukushima accident and LNG volumes are responsible for the increase in Japanese LNG price. Also, adjustment speed of error correction term shows that Japan's deviation from long-run equilibrium disappears faster than S. Korea does, indicating relatively strong Japanese linkage between LNG price and oil price.